Rice husk-derived nanosilica alleviates aluminum accumulation and toxicity in Brassica napus by regulating cellular metabolism and antioxidant defense - Raheel Munir; Nazia Jan; Bahar Ali; Rana Muhammad Amir Gulzar; Muhammad Haseeb Javaid; Iqbal Hussain; Yinbo Gan (Environmental Research, 2026)

Molecular approaches and chemical boundaries in bio-hybrid systems for synergistic remediation of heavy metals and microplastics in groundwater - Abdul Rehman; Sitian Ma; Haowen Xiao; Xiaojun Zheng; Samra Ijaz; Muhammad Zeeshan Gulzar; Muhammad Raza Farooq (Groundwater for Sustainable Development, 2026)

Green-Synthesized Zinc Oxide Nanoparticles from Selenicereus grandiflorus Exhibit Potent Nematicidal Activity Against Meloidogyne incognita - Sidra Ahmad; Mian Afaq Ahmad; Nayab Ahmad; Fazal Umer; Iqbal Munir; Md. Shahinoor Islam; Gulzar Ahmad; Muhammad Ijaz; Allah Ditta; Rashid Iqbal; Badr Aldahmash; Ahmed Rady (Current Microbiology, 2026)

Parametric optimization and mechanistic investigation of polyvinyl chloride microplastic degradation via an intensified hydrothermal Fenton reaction - Muhammad Zeeshan Gulzar; Guijian Liu; Muhammad Imran; Muhammad Arif; Samina Irshad; Bisma Sattar; Muhammad Irtaza Sajjad Haider; Huihui Zhou; Balal Yousaf (Journal of Water Process Engineering, 2026)

Synergistic photo-assisted AOPs using acid-modified biochar: Enhanced micropollutant levofloxacin degradation in industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Bisma Sattar; Muhammad Zeeshan Gulzar; Hameer Chand; Ruijia Liu (Desalination, 2026)

Farmyard manure mineralization: field and laboratory insights into manure placement depth and mulching strategies for sustainable maize production - Sarmad Iqbal; Ahmad Khan; Gulzar Ahmad; Habib Akbar; Dost Muhammad (Plant and Soil, 2026)

Calotropis Leaf Extract-Assisted Phytoextraction of Nickel Contaminated Soils - Muhammad Rizwan Shah; Gulzar Akhtar; Hafiz Nazar Faried; Muhammad Asif Shehzad; Amjad Farooq (Journal of Soil Science and Plant Nutrition, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Simultaneous quantification of hydroxycinnamate derivatives and antioxidant activity of Ziziphus oxyphylla Edgew. leaf methanolic extract - Surriya Naheed; Muhammad Wajid; Afsheen Ehsan; Khalid Hussain; Gulzar Muhammad; Naureen Shehzadi; Muhammad Tanveer Khan; Imran Ahmad; Adnan Ashraf (Natural Product Research, 2026)

Epidemiological, Morphometric, and Genetic Analysis of Pediculus humanus capitis (Head Lice) in Pakistan: Evidence of Regional Diversity and Global Admixture - Muhammad Ilyas; Ayesha Gulzar; Tayyaba Shan; Fazeela Manzoor; Uzma Bibi; Maria Komal; Sabika Firasat; Kiran Afshan (Acta Parasitologica, 2025)

Chitosan induces water deficit stress tolerance in Gladiolus grandiflorus via regulating water relations, gaseous exchange traits, and antioxidative defense - Muhammad Rizwan; Gulzar Akhtar; Muhammad Asif Shehzad; Salman Aloufi; Suliman Mohammed Suliman Alghanem; Faisal Zulfiqar; M. Nasir Khan; Özhan Şimşek; Fahad Al-Asmari; Mehmet Tütüncü; Tolga İzgü; Lala Gurbanova (Plant Biosystems, 2025)

The nexus between global value chains and productivity gains of ASEAN countries - Zia Ur Rahman; Wajid Khan; Musarat Abbas; Fatima Gulzar; Muhammad Azhar Farooq (Environment, Development and Sustainability, 2025)

Microplastic contamination in agricultural soils from mulch films and organic amendments: Transformation mechanism, soil-Biota toxicity, and future perspectives - Bisma Sattar; Guijian Liu; Balal Yousaf; Muhammad Arif; Muhammad Zeeshan Gulzar; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Samra Ijaz; Muhammad Awais Haider; Kiran Aziz (Waste Management, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Organic matter and microplastics nexus: A comprehensive understanding of the synergistic impact on soil health - Samra Ijaz; Guijian Liu; Abdul Rehman; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Bisma Sattar; Muhammad Zeeshan Gulzar; Sofia Nosheen; Balal Yousaf (Science of The Total Environment, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Hydrothermal integrated chemical treatment of microplastics for efficient degradation: Mechanistic insight and degradation behavior - Muhammad Zeeshan Gulzar; Guijian Liu; Balal Yousaf; Muhammad Imran; Muhammad Arif; Muhammad Nauman; Muhammad Irtaza Sajjad Haider; Bisma Sattar; Rabia Safeer; Samra Ijaz; Ruijia Liu (Journal of Water Process Engineering, 2025)

Diffused sunlight assisted green synthesis of silver nanoparticles using Cotoneaster nummularia polar extract for antimicrobial and wound healing applications - Nasir Assad; Muhammad Naeem-ul-Hassan; Muhammad Ajaz Hussain; Azhar Abbas; Muhammad Sher; Gulzar Muhammad; Yasir Assad; Muhammad Farid-ul-Haq (Natural Product Research, 2025)

Silent threats of lead-based paints in toys and households to children’s health and development - Muhammad Ubaid Ali; Muhammad Zeeshan Gulzar; Bisma Sattar; Sajeela Sehar; Qumber Abbas; Muhammad Adnan; Jingwei Sun; Zhuanxi Luo; Gongren Hu; Ruilian Yu; Ming Hung Wong (Journal of Hazardous Materials, 2025)

A comprehensive review on phytochemistry, pharmacology, preclinical, and clinical trials of Cydonia oblonga - Tuba; Muhammad Ajaz Hussain; Gulzar Muhammad; Muhammad Arshad Raza; Adnan Ashraf; Muhammad Tahir Haseeb; Muhammad Mushtaq; Zahid Shafiq (Phytochemistry Reviews, 2025)

Profusion of microplastics in dental healthcare units; morphological, polymer, and seasonal trends with hazardous consequences for humans - Naseem Akhtar; Arifa Tahir; Abdul Qadir; Rehana Masood; Zain Gulzar; Muhammad Arshad (Journal of Hazardous Materials, 2024)

Analyzing policy implications by considering adoption barriers on consumer adoption intention for electric vehicles: a comprehensive overview - Farheen Ehsan; Salman Habib; Muhammad Majid Gulzar; Junhua Guo (Environment, Development and Sustainability, 2024)

A comprehensive review of plant-based mucilages as promising candidates for water remediation - Sehar Javed; Zarfishan Zulfiqar; Zain Fatima; Gulzar Muhammad; Muhammad Ajaz Hussain; Muhammad Mushtaq; Muhammad Tahir Haseeb (Journal of Environmental Chemical Engineering, 2024)

Synthesis and characterization of Ca-alginate/CuO bionanocomposite for removal of Reactive Yellow 145 dye: a green approach towards sustainability - Saman Shams; Shumaila Kiran; Tahsin Gulzar; Muhammad Naveed Anjum (Clean Technologies and Environmental Policy, 2024)

Antioxidative enzymes, phytochemicals and proximate components in jujube fruit (Ziziphus mauritiana L.) with respect to genotypes and harvest maturity - Zohaib Asghar; Muhammad Amin; Sami Ullah; Hamad Hassan; Umm-e Habiba; Kashif Razzaq; Ishtiaq Ahmad Rajwana; Gulzar Akhtar; Hafiz Nazar Faried; Muhammad Aiyub; Shafa Nayab; Ambreen Naz; et al. (Food Bioscience, 2024)

Green synthesis, properties, and biomedical potential of gold nanoparticles: A comprehensive review - Zain Fatima; Ramsha Saleem; Rana Rashad Mahmood Khan; Maira Liaqat; Muhammad Pervaiz; Zohaib Saeed; Gulzar Muhammad; Muhammad Amin; Shahzad Rasheed (Biocatalysis and Agricultural Biotechnology, 2024)

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

Clubroot (Plasmodiophora brassicae) Suppression Under Biocontrol Agents in Pak choi with Variations in Physiological, Biochemical, and Bacterial Diversity - Shazma Gulzar; Fiza Liaquat; Muhammad Khalid Hameed; Asad Rehman; Muhammad Salman Zahid; Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Yidong Zhang (Journal of Plant Growth Regulation, 2024)

Renewable energy and green economic growth nexus: Insights from simulated dynamic ARDL - Saira Ashfaq; Song Liangrong; Fahad Waqas; Saqib Gulzar; Ghulam Mujtaba; Rana Muhammad Nasir (Gondwana Research, 2024)

Scorpion sting in Hafizabad, Pakistan: Facility based epidemiological study - Muhammad Mohsin Ahsan; Zoya Gulzar; Hafiz Muhammad Tahir; Aamir Ali; Muhammad Ismail; Muhammad Khalid Mukhtar; Zain Ul Abdin (Toxicon, 2024)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Differential Response of Two Contrasting Melon (Cucumis melo L.) Genotypes to Drought Stress - Asad Rehman; Jinyang Weng; Pengli Li; Jing Yu; Saeed ur Rahman; Muhammad Khalid; Iftikhar Hussain Shah; Shazma Gulzar; Liying Chang; Qingliang Niu (Journal of Plant Biology, 2023)

Effects of melatonin and Trichoderma harzianum on pak choi yield, chlorophyll contents and antioxidant defense system under clubroot disease - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Iftikhar Hussain Shah; Asad Rehman; Muhammad Khalid Hameed; Samiah Arif; Xuanwei Zhou; Yidong Zhang (South African Journal of Botany, 2023)

Visible light-driven photocatalytic bacterial inactivation on PPE, supported by the DFT and bactericidal study - Gulzar Ahmed; Adeel Rasheed; Khurram Shahzad Munawar; Satesh Bandaru; Javid Khan; Zhongwu Liu; Muhammad Sheraz Ahmad (Environmental Science and Pollution Research, 2023)

Endophytic bacterial diversity by 16S rRNA gene sequencing of Pak choi roots under fluazinam, Trichoderma harzianum, and Sophora flavescens inoculation - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Muhammad Salman Zahid; Samiah Arif; Xuanwei Zhou; Yidong Zhang (Functional & Integrative Genomics, 2023)

Biogenic synthesis and characterization of ZnO nanoparticles for degradation of synthetic dyes: A sustainable environmental cleaner approach - Atizaz Rasool; Shumaila Kiran; Tahsin Gulzar; Shazia Abrar; Abdul Ghaffar; Muhammad Shahid; Sofia Nosheen; Saba Naz (Journal of Cleaner Production, 2023)

Plant-assisted synthesis and characterization of MnO2 nanoparticles for removal of crystal violet dye: an environmental remedial approach - Muniba Rahmat; Shumaila Kiran; Tahsin Gulzar; Mohd Yusuf; Rabia Nawaz; Javaira Khalid; Nooria Fatima; Ata Ullah; Muhammad Azam (Environmental Science and Pollution Research, 2023)

Phytotoxic effects of chemically synthesized copper oxide nanoparticles induce physiological, biochemical, and ultrastructural changes in Cucumis melo - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fiza Liaquat; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Science and Pollution Research, 2023)

A green and environmental sustainable approach to synthesis the Mn oxide nanomaterial from Punica granatum leaf extracts and its in vitro biological applications - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Monitoring and Assessment, 2022)

Consumption of Citrus mealybug, Planococcus citri by two predators, Cryptolaemus montrouzieri Mulsant and Chrysoperla carnea (Stephen), under controlled conditions - Rehana Bibi; Munir Ahmad; Asim Gulzar; Muhammad Tariq; Muneer Ahmad (International Journal of Tropical Insect Science, 2022)

Types, sources, socioeconomic impacts, and control strategies of environmental noise: a review - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Allah Ditta; Predrag Ilic; Muhammad Amin; Abdul Basit Naveed; Aadil Gulzar (Environmental Science and Pollution Research, 2022)

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

Pretreatment with Chitosan Arbitrates Physiological Processes and Antioxidant Defense System to Increase Drought Tolerance in Alfalfa (Medicago sativa L.) - Ghulam Mustafa; Muhammad Asif Shehzad; M. Hammad Nadeem Tahir; Fahim Nawaz; Gulzar Akhtar; Muhammad Asaad Bashir; Abdul Ghaffar (Journal of Soil Science and Plant Nutrition, 2022)

Evaluation of insecticidal activity of Beauveria bassiana against different instar larvae of Plutella xylostella by using two different methods of application - Muhammad Shehzad; Muhammad Tariq; Qurban Ali; Asad Aslam; Tariq Mukhtar; Muhammad Faheem Akhtar; Asim Gulzar; Muhammad Faisal (International Journal of Tropical Insect Science, 2022)

Re-investigating the nexuses of renewable energy, natural resources and transport services: a roadmap towards sustainable development - Syed Abdul Rehman Khan; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Amir Rafique; Mustansar Hayat; Saqib Gulzar; Zhang Yu (Environmental Science and Pollution Research, 2022)

Correction to: Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Ameliorative mechanisms of turmeric-extracted curcumin on arsenic (As)-induced biochemical alterations, oxidative damage, and impaired organ functions in rats - Anam Ishaq; Huma Gulzar; Ali Hassan; Muhammad Kamran; Muhammad Riaz; Aasma Parveen; Muhammad Sohaib Chattha; Noman Walayat; Sana Fatima; Sobia Afzal; Shah Fahad (Environmental Science and Pollution Research, 2021)

Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafiz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Effect of profenofos and citrus oil on Cryptolaemus montrouzieri Mulsant and Chrysoperla carnea Stephens, key predators of citrus mealybug, Planococcus citri (Risso), under laboratory conditions - Rehana Bibi; Munir Ahmad; Asim Gulzar; Muhammad Tariq (International Journal of Tropical Insect Science, 2021)

The effect of expected financial performance on corporate environmental responsibility disclosure: evidence from China - Yanqi Zeng; Muhammad Awais Gulzar; Zongjun Wang; Xinxin Zhao (Environmental Science and Pollution Research, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Estimation of forest carbon stocks in temperate and subtropical mountain systems of Pakistan: implications for REDD+ and climate change mitigation - Anwar Ali; Muhammad Irfan Ashraf; Saeed Gulzar; Muhammad Akmal (Environmental Monitoring and Assessment, 2020)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

MPD3: a useful medicinal plants database for drug designing - Arooj Mumtaz; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Farooq Anwar; Faisal Gulzar; Muhammad Amjad Ali; Nazamid Saari; Muhammad Tariq Pervez (Natural Product Research, 2017)

Differences in photosynthetic syndromes of four halophytic marsh grasses in Pakistan - Muhammad Moinuddin; Salman Gulzar; Abdul Hameed; Bilquees Gul; M. Ajmal Khan; Gerald E. Edwards (Photosynthesis Research, 2017)

Variability of aerosol optical depth over Swat in Northern Pakistan based on satellite data - Khan Alam; Rehana Khan; Shahid Ali; Muhammad Ajmal; Gulzar Khan; Wazir Muhammad; Malak Azmat Ali (Arabian Journal of Geosciences, 2015)